Nematode Biotic Indices: Advancements and Applications in Assessing Soil Health (Indian Journal of Nematology, 2024)
Nematodes are a miracle of evolution with unmatched ecological competence. In soil ecosystems, nematodes are the most abundant and diverse metazoans. Nematodes are present at different trophic levels in soil food webs, ranging from grazers of microorganisms functioning at the interface of living and non-living matter in detritus food webs to parasites of higher plants and animals. Soil nematodes regulate key ecological processes and services. Nematodes regulate primary production, predation, energy transfer, decomposition of organic matter, and nutrient mineralization in agricultural ecosystems directly by feeding on crop plants and indirectly by consuming microflora and fauna. The nematode community in soil, therefore, has a high information content. Nematodes have several characteristics of good bioindicators including ubiquitous presence, a direct relationship between structure and function, diverse trophic groups, a wide range of life history strategies, and the availability of well-tested biotic indices. Nematode biotic indices have progressed over time, evolving from simple community indices based on counts (abundance, frequency, etc.) to specialized maturity indices based on colonizer and persister traits (Maturity Index, Plant Parasite Index, etc.), and further to the more advanced indices based on functional guilds (Enrichment Index, Basal Index Structure Index, etc.) that are valuable in soil food web diagnostics. The most advanced index, the metabolic footprint, estimates nematode contribution to a variety of environmental services and processes. Classical and molecular approaches to nematode community analysis are used for assessing the impact of various kinds of disturbances in the soil environment. Nematode biotic indices have been successfully employed as environmental bioindicators to measure the impact of biological, chemical, and physical factors on soil health. and ecosystem services in both natural and managed ecosystems. The available evidence emphasizes the significance of nematodes as bioindicators and their potential for widespread application. The specific characteristics that make nematodes useful bioindicators, the evolution of nematode biotic indices, tools for computing and interpreting these indices, and recent trends in the application of nematode biotic indices in assessing soil health and ecosystem disturbance caused by various agents are discussed in this paper.